Benjamin D. Koen (ed.), The Oxford Handbook of Medical Ethnomusicology (2008) (Journal of the Society for Musicology in Ireland, 2010)
Review of Benjamin D. Koen (ed.), The Oxford Handbook of Medical Ethnomusicology (Oxford: Oxford University Press, 2008), ISBN 978-0-19-533707-5